Draft Annual Plan 2003-04 Scheme-Wise Proposed Plan Outlay National Capital Territory of Delhi - Planning Commission (Planning Commission, 2003)
Sector-wise Plan Outlay, Agency -wise Plan Outlay, Sector/Deptt-wise Plan Outlay, Sector/Scheme-wise Plan Outlay, Agr. and Allied Services, Co-operation, Rural Development, Minor Irrigation, Flood Control, Energy.
Planning Department, Government of N.C.T. of Delhi